2008
DOI: 10.1007/s00270-008-9384-7
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Radiofrequency Ablation in Patients with Hepatic Metastases from Breast Cancer

Abstract: The purpose of this study was to evaluate technical success, technique effectiveness, and survival following radiofrequency ablation for breast cancer liver metastases and to determine prognostic factors. Forty-three patients with 111 breast cancer liver metastases underwent CT-guided percutaneous radiofrequency (RF) ablation. Technical success and technique effectiveness was evaluated by performing serial CT scans. We assessed the prognostic value of hormone receptor status, overexpression of human epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 33 publications
7
42
0
Order By: Relevance
“…[47].The third largest study (N=43) showed similar figures, i.e. MOS 59 months; and 3-and 5-year survivals were 75% and 38%, respectively [48].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 66%
See 2 more Smart Citations
“…[47].The third largest study (N=43) showed similar figures, i.e. MOS 59 months; and 3-and 5-year survivals were 75% and 38%, respectively [48].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 66%
“…Thus, the annual average was 1 -23 treatments (median 2). Three institutions had an annual average exceeding four [43,47,48]. The rate of synchronous metastases were 0-19% (reported in 3/7 studies).…”
Section: Studies Of Local Ablation (N=7)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some cases may not be suitable for US guidance due to tumor invisibility, high risk of collateral thermal injury, or absence of a safe electrode path [2]. In such cases, CT is a valid alternative [3] even though it may be challenging especially for ''hard-to-reach'' lesions (i.e., lesions of the hepatic dome, very small lesions) due to lack of real-time guidance.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest and most frequent site of BC metastasis is the bones and lungs, and no more than 5%e20% of cases have only liver metastases [3]. Metastatic BC is worldwide considered a systemic disease and therefore treated with chemotherapy [4].…”
Section: Introductionmentioning
confidence: 99%